Porokeratosis ptychotropica: Dermoscopy, reflectance confocal microscopy, and histopathological correlation - Francesco Lacarrubba; Maria Letizia Musumeci; Anna Elisa Verzì; Claudia Poma; Rosario Caltabiano; Giuseppe Micali (Wolters Kluwer Medknow Publications, 2021)
Porokeratosis ptychotropica (PP) is a rare variant of porokeratosis characterized by pruritic, symmetrical, red-brown verrucous papules, and plaques most commonly localized within the gluteal fold. Herein, we report the clinical, dermoscopy, and reflectance confocal microscopy (RCM) aspects of a case of PP in a 63-year-old Caucasian woman along with histopathological correlation. Both dermoscopy and RCM were able to recognize the cornoid lamella, the histopathological clue shared by all clinical variants of porokeratosis. These non-invasive techniques may help in the differential diagnosis with other inflammatory/infectious and neoplastic disorders that may clinically resemble PP, but show distinct patterns.